Demokracja w początkach XXI wieku. Jacques Ranciere o „władzy” demosu w demokracji i o postdemokracji - Kaczorowski, Paweł (Studia Polityczne, 2022)
The article introduces general issues covered by the new concept of post-democracy. It concerns the radical criticism of modern democracy functioning in systemic forms such as liberal democracy, the democratic state of law and consensual democracy. This criticism is undertaken by a group of leading researchers including Giorgio Agamben, Alain Badiou, Étienne Balibar, Maurice Blanchot, Judith Butler, Ernesto Laclau, Claude Lefort, Jean--François Lyotard, Chantal Mouffe, Jean-Luc Nancy, Antonio Negri, Slavoj Žižek and Jacques Rancière. The article presents the views of Jacques Rancière, one of the main thinkers on post-democracy. He has been selected because he presents his critique of modern democracy insightfully, using language that refers to the tradition of European philosophy. Rancière believes that in contemporary democracy its basic subject – demos – becomes increasingly invisible and unrecognised, and that it is impossible to argue about the participation of entities in demos, a dispute that constitutes the essence of democracy and modern politics. He thinks that contemporary democracy obscures its true character and thus falsifies it, at the same time as invariably referring to its ethos. The reasoning presented in this article is an immanent analysis of Jacques Rancière’s texts, particularly La mesentante (1995) and also La haine de la democratie (2005) and Dix theses sur la politique (in: idem Aux bords du politique, 1998). The author suggests that these works contain reasons that should encourage in-depth reflection on contemporary democracy, particularly as referring to demos in the practice of political democracy is nowadays often considered a harmful mistake, giving rise to accusations of populism.